2023
DOI: 10.1007/s11249-023-01770-z
|View full text |Cite
|
Sign up to set email alerts
|

Insights of the Ultralow Wear and Low Friction of Carbon Fiber Reinforced PTFE in Inert Trace Moisture Environment

Abstract: Ultralow wear rates and low friction have been observed for carbon fiber reinforced PTFE (CF/PTFE) when sliding against steel or cast iron in dry gas environments. Although the strong environmental sensitivity of this tribosystem is well known, the origin of the outstanding tribological performance in dry gas remains unanswered. Some researchers attribute the low friction and wear to the formation of carbon-rich surfaces in the absence of oxygen and moisture in the environment. However, low friction between ca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 72 publications
0
0
0
Order By: Relevance
“…The counterface discs were machined from 34CrNiMo6 alloy steel with a hardness of 460 HV. This material has been extensively studied as a counterface material for CF/PTFE composites and has shown favorable results [7,9,18]. The counterfaces were grinded to a surface roughness of S a = 0.12 ± 0.02 µm and a random texture, using 400 p silicon carbide abrasive paper in a figure-eight motion.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The counterface discs were machined from 34CrNiMo6 alloy steel with a hardness of 460 HV. This material has been extensively studied as a counterface material for CF/PTFE composites and has shown favorable results [7,9,18]. The counterfaces were grinded to a surface roughness of S a = 0.12 ± 0.02 µm and a random texture, using 400 p silicon carbide abrasive paper in a figure-eight motion.…”
Section: Methodsmentioning
confidence: 99%
“…The friction and wear of PTFE composites filled with carbon fiber or other carbons are currently unchallenged in dry gas environments compared to other fillers [5,6]. The mechanism behind the great tribological performance of CF/PTFE sliding against steel in dry gas has recently been discovered by the authors [7]. In high-purity nitrogen, a super smooth iron fluoride film is tribochemically formed on the steel surface, which has poor adhesion to the non-graphitic carbon film that is formed on the CF/PTFE surface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many scholars at home and abroad have made important contributions to the development of this direction. Luo's group discovered several water-based liquid very-low-friction systems [97,98], and Liu and Zhang's group discovered an amorphous, fullerene-carbon film, solid, very-low-friction system [99]. Direct experimental determination of the dissociation energy of graphene in self-retraction motion was independently achieved by E. Koren's group [100] and Quanshui Zheng's group [101].…”
Section: Unique Properties Of Superlubricitymentioning
confidence: 99%
“…However, so far, very little has been reported regarding the tribological characteristics of a reinforced thermoplastic filled with a solid lubricant, and very few articles among them are concerned with composites prepared by the SLS technique [15,[24][25][26]. The few reported results showed that inclusion of either PTFE or MoS 2 could effectively reduce the coefficient of friction of laser-sintered PA12 by forming a homogenous transfer film on the counter-surface [15,27], and that a 5-10% weight fraction of graphite was sufficient to significantly improve the tribological characteristics of PA6 [24].…”
Section: Introductionmentioning
confidence: 99%